2004
DOI: 10.1007/s11661-004-0071-2
|View full text |Cite
|
Sign up to set email alerts
|

Tensile and fatigue behavior of Al-based metal matrix composites reinforced with continuous carbon or alumina fibers: Part I. Quasi-unidirectional composites

Abstract: The thermomechanical (dilatometric, tensile, and fatigue) behavior of Al-based metal matrix composites (MMCs) is investigated. These composites are reinforced by quasi-unidirectional (quasi-UD) woven fabric preforms with 90 pct of continuous fibers in the longitudinal direction and 10 pct in the transverse direction. The two composite systems investigated feature a highly ductile matrix (AU2: Al-2Cu wt pct) with a strongly bonded fiber-matrix interface (N610 alumina fibers) and an alloyed, high-strength matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 30 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…This method was widely used to fabricate aluminum matrix composites [2]. It can be used to fabricate many kinds of C/Al composites, such as continuous [23,[78][79][80][81][82][83] or short [37,60,84,85] carbon fibers/Al composites, VGCFs/Al composites [64,86], graphite/Al composites [66,[87][88][89], diamond/Al composites [90,91,92], etc.…”
Section: Gas Pressure Infiltrationmentioning
confidence: 99%
See 1 more Smart Citation
“…This method was widely used to fabricate aluminum matrix composites [2]. It can be used to fabricate many kinds of C/Al composites, such as continuous [23,[78][79][80][81][82][83] or short [37,60,84,85] carbon fibers/Al composites, VGCFs/Al composites [64,86], graphite/Al composites [66,[87][88][89], diamond/Al composites [90,91,92], etc.…”
Section: Gas Pressure Infiltrationmentioning
confidence: 99%
“…Jacquesson et al [80] used gas pressure infiltration to fabricate K139 carbon fibers reinforced A357 aluminum alloys (V f = 58%) with tensile strength and modulus of 1,083 MPa and 395 GPa, respectively, but the fabrication parameters are not given. However, it was also found that carbon fibers/Al composites fabricated by this process exhibited relatively poor properties [78,81,82], which indicate that it is a difficult task to fabricate carbon fibers/ Al composites by optimizing the fabrication parameters.…”
Section: Gas Pressure Infiltrationmentioning
confidence: 99%
“…Ceramic and carbon based strengthening are mostly used to further enhance aluminium alloy's mechanical, tribological and physical characteristics. The fortifications like fibres of graphite (P-55) [6], carbon fiber packs (K139) [7] and SiC particles [8,9] of various dimensions were utilized to strengthen different aluminium alloys. Metal Matrix Composites (MMC) with aluminium or its alloy as the matrix are gaining broad prevalence in numerous categories owing to their enhanced mechanical characteristics along with lower density, particularly when endurance and weight are of primary significance.…”
Section: Introductionmentioning
confidence: 99%
“…Friction coefficient and wear loss decreased as the carbon fiber volume fraction increased [16]. Tensile and shear properties, fatigue performance, and fracture toughness of such composites are also investigated, specifically for the effect of interfacial bonding conditions on the mechanical properties of the composite [17][18][19][20][21]. Studies have shown that the heat treatment of the composite to achieve precipitation hardening in the matrix can lead to sufficient residual thermal stresses to damage the fibers [11].…”
Section: Introductionmentioning
confidence: 99%